Analysis of the Effect of Contractor Safety Management System (CSMS) on Health and Safety Culture at PT. Indocement Tunggal Prakarsa Tbk - Abdul Rohim Tualeka; Aulia Rahman Farizky Pujiantara; Barikly Robby (Syntax Corporation, 2023)
It is known that there are several losses in the company's operating activities caused by the performance of contractors who have little understanding of occupational health and safety (OHS). Negligence by contractors can pose danger to the company's operations and cause accidents. therefore activities of contractors must be managed properly to ensure safety in every work activity on contractors, so it requires the management of contractor workers, namely the Contractor Safety Management System (CSMS). The method used in this research is a descriptive qualitative analysis method of in-depth interviews, distribution of questionnaires, and field observations. The data will then be analyzed. Result: From the analysis that has been carried out, the results of research by interviewing workers, the implementation of CSMS began in 2014. PT Indocement Tunggal Prakarsa, Tbk experienced a drastic reduction in lost time injury to zero accidents Where before the CSMS implementation, accidents were very frequent; 56 accidents in 2008 and 56 accidents in 2009. In conclusion, PT Indocement Tunggal Prakarsa, Tbk has implemented CSMS properly and adequately. PT. Indocement Tunggal Prakarsa, Tbk involving contractor workers in the most questionnaire results are Accident and Near Accident Investigations, Safety Monitoring, Safety Talks, Making Work Permits and Hazardous Work Permits, Equipment Certification, Emergency Response, Personal Protective Equipment The factors that affect the effectiveness of CSMS implementation the most are training factors, communication factors, and behavioral factors, this can be seen in fewer rejections from respondents regarding the contents of the questionnaire